2021
DOI: 10.1016/j.ijid.2021.02.085
|View full text |Cite
|
Sign up to set email alerts
|

Less severe course of COVID-19 is associated with elevated levels of antibodies against seasonal human coronaviruses OC43 and HKU1 (HCoV OC43, HCoV HKU1)

Abstract: The clinical course of COVID-19 is very heterogeneous: Most infected individuals can be managed in an outpatient setting, but a substantial proportion of patients requires intensive care, resulting in a high rate of fatalities. We performed a biomarker study to assess the impact of prior infections with seasonal coronaviruses on COVID-19 severity. 60 patients with confirmed COVID-19 infections were included (age 30 - 82 years; 52 males, 8 females): 19 inpatients with critical disease, 16 inpatients with severe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 9 publications
2
27
1
Order By: Relevance
“…Diagnosis followed the clinical description released by the World Health Organization (14). COVID-19 patients were confirmed by the use of SARS-CoV-2specific RT-PCR analysis of oropharyngeal and nasopharyngeal swabs (28). Patients having acute disease (n = 32) were hospitalized in the university clinic, including interventions at ICU (n = 15).…”
Section: Patientsmentioning
confidence: 99%
“…Diagnosis followed the clinical description released by the World Health Organization (14). COVID-19 patients were confirmed by the use of SARS-CoV-2specific RT-PCR analysis of oropharyngeal and nasopharyngeal swabs (28). Patients having acute disease (n = 32) were hospitalized in the university clinic, including interventions at ICU (n = 15).…”
Section: Patientsmentioning
confidence: 99%
“…This finding is in line with one previous study showing that even in advanced age, an immunological memory against SARS-CoV-2 was developed and was still present in most patients months after recovery [ 27 , 38 , 39 , 40 , 41 ]. Another potential explanation may be that older patients may had more repetitive exposures to seasonal coronaviruses that can induce cross-reactive T cells and antibodies recognizing regions of the Membrane (M) or Spike (S) proteins, which are conserved among several coronaviruses [ 42 , 43 ]. Especially, the Membrane (M) protein accounting for the overall shape of the viral envelope is the most abundant structural protein of the coronavirus family.…”
Section: Discussionmentioning
confidence: 99%
“…noted that a less severe course of COVID-19 was associated with elevated levels of antibodies against endemic coronaviruses. 53 They concluded that prior infections with endemic coronaviruses might protect against a severe course of disease. Gouma et al.…”
Section: Antibody Responses Against Sars-cov-2mentioning
confidence: 99%